PENGARUH pH TERHADAP STABILITAS OKSIDATIF DAN EFEKTIVITAS ANTIOKSIDAN DALAM SISTEM EMULSI - Fatimah, Feti (Sam Ratulangi University, 2008)
The oxidation of lipids in emulsified form is more complex than that in bulk lipid. In Emulsion form, thereare more variables influencing lipid oxidation, including oil proportion, type and concentration of emulsifier,pH and buffer system. The aims of this research were to study the effect of pH on oxidative stability andeffectiveness of antioxidants of emulsion system. The oxidative stability and antioxidants effectiveness inthis system were determined by hydroxyperoxydes content. The result showed that reduction pH from 5,7to 3,7 could reduce its oxidative stability. The pKa of antioxidants also influenced their effectiveness on theemulsion systemÂ Keywords: oxidative stability, antioxidant, emulsion, pH, hydroxyperoxydes